Common Β- Thalassaemia Mutations in - P Azarfam (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2005)
Introduction: β –Thalassaemia was first explained by Thomas Cooly as Cooly’s anaemia in 1925. The β- thalassaemias are hereditary autosomal disorders with decreased or absent β-globin chain synthesis. The most common genetic defects in β-thalassaemias are caused by point mutations, micro deletions or insertions within the β-globin gene. Material and Methods: In this research , 142 blood samples (64 from childrens hospital of Tabriz , 15 samples from Shahid Gazi hospital of Tabriz , 18 from Urumia and 45 samples from Aliasghar hospital of Ardebil) were taken from thalassaemic patients (who were previously diagnosed ).Then 117 non-familial samples were selected . The DNA of the lymphocytes of blood samples was extracted by boiling and Proteinase K- SDS procedure, and mutations were detected by ARMS-PCR methods. Results: From the results obtained, eleven most common mutations,most of which were Mediterranean mutations were detected as follows; IVS-I-110(G-A), IVS-I-1(G-A) ،IVS-I-5(G-C) ,Frameshift Codon 44 (-C,( codon5(-CT),IVS-1-6(T-C), IVS-I-25(-25bp del) ,Frameshift 8.9 (+G) ,IVS-II-1(G-A) ,Codon 39(C-T), Codon 30(G-C) the mutations of the samples were defined. The results showed that Frameshift 8.9 (+G), IVS-I-110 (G-A) ,IVS-II-I(G-A), IVS-I-5(G-C), IVS-I-1(G-A) , Frameshift Codon 44(-C) , codon5(-CT) , IVS-1-6(T-C) , IVS-I-25(-25bp del) with a frequency of 29.9%, 25.47%,17.83%, 7.00%, 6.36% , 6.63% , 3.8% , 2.5% , 0.63% represented the most common mutations in North - west Iran. No mutations in Codon 39(C-T) and Codon 30(G-C) were detected. Cunclusion: The frequency of the same mutations in patients from North - West of Iran seems to be different as compared to other regions like Turkey, Pakistan, Lebanon and Fars province of Iran. The pattern of mutations in this region is more or less the same as in the Mediterranean region, but different from South west Asia and East Asia.